MAKTABGACHA YOSHDAGI KOXLEAR IMPLANTLI BOLALARNI NUTQIY REABILITATSIYASI (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article examines the importance of cochlear implantation for children with hearing impairments and focuses on speech rehabilitation of preschool children with cochlear implants. The structure and functioning of the cochlear implant, as well as the main indications for implantation, are described. The stages of post-implantation habilitation, speech therapy, and corrective pedagogical work are analyzed. Special attention is given to the development of auditory speech perception, sound discrimination, pronunciation skills, vocabulary enrichment, and grammatical language development in preschool-aged children. The role of cooperation between specialists and families in the speech rehabilitation process is emphasized. The findings highlight the necessity of a systematic and individualized approach to support speech development and social integration of children with cochlear implants.